Au nanoparticles-doped g-C3N4 nanocomposites for enhanced photocatalytic performance under visible light illumination. Issue 14 (1st October 2020) - Faisal, M.; Jalalah, Mohammed; Harraz, Farid A.; El-Toni, Ahmed Mohamed; Khan, Aslam; Al-Assiri, M.S.
Abstract: Surface and bandgap engineering of graphitic carbon nitride (g-C3 N4 ) could be vital in enhancing photocatalytic performance by suppressing the recombination rate of photogenerated electron-hole pairs. The present report investigated the doping effects of various wt.% (0.2–5.0%) of gold nanoparticles (Au NPs) to g-C3 N4 (Au/g-C3 N4 ) for the enhancement of the photocatalytic efficiency of g-C3 N4 nanocomposites. A straightforward and cost-effective synthesis methodology has been applied for the desired nanocomposites. Relevant characterization tools such as XRD, XPS, TEM, FTIR, and UV–Vis were utilized to analyze various physicochemical properties. The TEM images clearly show that spherical Au NPs were homogeneously distributed into the thin carbon nitride graphitic layers, confirming the successful doping of Au. The higher-magnification TEM image confirms that the sizes of the Au NPs varied from 15 to 25 nm. The photoactivity of the newly designed Au/g-C3 N4 nanocomposites has been evaluated for the degradation of both methylene blue dye and the drug gemifloxacin mesylate, and their efficiencies were compared with that of bare g-C3 N4 . Our findings revealed that Au/g-C3 N4 nanocomposites with various Au contents had superior photocatalytic activity compared to bare g-C3 N4 . However, the 1%Au/g-C3 N4 nanocomposite could be considered the optimum photocatalyst, producing 95.13% destruction of the target dye molecule in 90 min, in contrast to the 69% achieved with bare g-C3N4, under the clean energy of visible light illumination. Additionally, the photodegradation rate of the 1%Au/g-C3 N4 nanocomposite is 2.69 times higher than the rate of bare g-C3 N4 . This report might open a new gateway towards a straightforward and cost-effective synthesis approach for Au/g-C3 N4 nanocomposites and provides a smooth and robust platform for the utilization of this new nanocomposite for environmental remediation processes.